Measurement of K-shell absorption jump factors and jump ratios in some lanthanide elements using EDXRF technique - Polat, Recep; Icelli, Orhan; Yalcin, Zeynel; Pesen, Erhan; Orak, Salim (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
59.5 keV gamma rays scattered by an aluminum foil have been used as a radiation source to measure the absorption jump factor and jump ratios for absorbers Ce, Pr, Nd, Sm, Eu and Tb. The theoretical and experimental values are compared with the corresponding ones in the literature. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Jump factor; Jump ratio; The mass attenuation coefficient; Lanthanide elements; X-RAY-ABSORPTION; RADIATION MEASUREMENTS 39; ATTENUATION; AG; PARAMETERS; BA; CS; KARABULUT; ERTUGRUL; POLAT; Nuclear Science & Technology